2011
DOI: 10.1105/tpc.110.081307
|View full text |Cite
|
Sign up to set email alerts
|

Chilling of Dormant Buds HyperinducesFLOWERING LOCUS Tand Recruits GA-Inducible 1,3-β-Glucanases to Reopen Signal Conduits and Release Dormancy inPopulus   

Abstract: In trees, production of intercellular signals and accessibility of signal conduits jointly govern dormancy cycling at the shoot apex. We identified 10 putative cell wall 1,3-b-glucanase genes (glucan hydrolase family 17 [GH17]) in Populus that could turn over 1,3-b-glucan (callose) at pores and plasmodesmata (PD) and investigated their regulation in relation to FT and CENL1 expression. The 10 genes encode orthologs of Arabidopsis thaliana BG_ppap, a PD-associated glycosylphosphatidylinositol (GPI) lipid-anchor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
535
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 427 publications
(560 citation statements)
references
References 73 publications
(118 reference statements)
22
535
1
2
Order By: Relevance
“…Homologies to vernalization have been invoked, but critical differences exist because the vernalization-associated epigenetic mechanism requires sustained division, whereas bud dormancy can be imposed and reset in the same meristem cells (2). Recently, it has been shown that the plasmodesmata connections to the meristem are plugged during dormancy and need to be reopened before growth-promoting signals like FT can reach their target's tissues in the apex (22). Expression of cell-cycle marker genes indicates that after endodormancy establishment, cambium meristem cells are arrested in the G1/S transition and unable to respond to growth-permissive conditions (23).…”
mentioning
confidence: 99%
“…Homologies to vernalization have been invoked, but critical differences exist because the vernalization-associated epigenetic mechanism requires sustained division, whereas bud dormancy can be imposed and reset in the same meristem cells (2). Recently, it has been shown that the plasmodesmata connections to the meristem are plugged during dormancy and need to be reopened before growth-promoting signals like FT can reach their target's tissues in the apex (22). Expression of cell-cycle marker genes indicates that after endodormancy establishment, cambium meristem cells are arrested in the G1/S transition and unable to respond to growth-permissive conditions (23).…”
mentioning
confidence: 99%
“…In contrast, the transition from dormancy to active growth is characterized by the induction of flowering pathways, RNA metabolism and protein biosynthesis and transport (Larisch et al 2012). It has been found that SAM cells are symplastically isolated during the dormant period due to the formation of a callose block at the plasmodesmata (Rinne and van der Schoot 1998;Rinne et al 2001;Rinne et al 2011). However, it is not yet clear whether there is a causal relationship between the cellular isolation and the activity-dormancy cycle.…”
Section: Approaching Tree Architecturementioning
confidence: 99%
“…Additionally, the circadian clock might be able to sense temperature in Arabidopsis (Edwards et al 2006;Gould et al 2006). In Populus, FT2 controls growth cessation, bud set and dormancy induction, and FT1 is expressed during the chilling period to induce the transition from the vegetative to the reproductive phase (Böhlenius et al 2006, Hsu et al 2006Rinne et al 2011). Furthermore, overexpression of CEN/TFL1 in Populus causes delayed bud break and altered chilling requirements (Mohamed et al 2010).…”
Section: Approaching Tree Architecturementioning
confidence: 99%
“…For example, it has been reported that in perennial trees the release of bud dormancy requires the removal of callose in the plamodesmata in order to restore the symplastic connectivity in the meristem (Rinne et al 2011;Rinne et al 2001;Rinne et al 2016). Although we saw there is a vascular connection between the buds and the mother bulb, it is plausible to think that it might not be very functional when callose is not entirely removed from plasmodesmata in dormant buds, and therefore less carbon resources can be remobilized into those buds.…”
Section: Dormancy and Sink Strength In Tulip Axillary Budsmentioning
confidence: 99%